2010
DOI: 10.4166/kjg.2010.55.4.232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combination Pretreatment of Polyethylene Glycol Solution and Magnesium Hydroxide for Colonoscopy

Abstract: Bowel preparation with magnesium hydroxide and 4 liters of PEG solution might reduce solid stool in constipation group, but could not improve preparation quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Studies have shown that some drugs, such as magnesium hydroxide 24 and bisacodyl, could be helpful for bowel preparation in patients with constipation, especially those with slow CTT. 25 26 Therefore, we suggest that these medications could be helpful for bowel preparation in patients with slow CTT.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that some drugs, such as magnesium hydroxide 24 and bisacodyl, could be helpful for bowel preparation in patients with constipation, especially those with slow CTT. 25 26 Therefore, we suggest that these medications could be helpful for bowel preparation in patients with slow CTT.…”
Section: Discussionmentioning
confidence: 99%
“…103 Polyethylene glycol (PEG) solution plus magnesium hydroxide induced more significantly effective colonic preparation in constipated patients, compared with PEG solution alone. 104 In conclusion, few studies have examined the effect of magnesium hydroxide, but many clinicians believe that it improves stool frequency and consistency in patients with normal renal function.…”
Section: Statement: Magnesium Salts Improve Stool Frequency and Consimentioning
confidence: 99%
“…Combining magnesium hydroxide with another laxative may improve these side effects by reducing the dose of both laxatives. Shin et al (2010) found that the combined administration of magnesium hydroxide and PEG increased bowel clearance compared with PEG treatment alone during colonoscopy in patients with constipation. Similarly, the combination of magnesium hydroxide and lactulose significantly improved stool parameters and increased total SCFA production, including acetic acid, compared with lactulose alone ( Fig.…”
Section: Discussionmentioning
confidence: 96%